Multi-dimensional force measurement binding used during skating in cross-country skiing - Linnamo, V.; Ohtonen, O.; Stöggl, T.; Komi, P.; Müller, E.; Lindinger, S. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
In classic cross-country skiing leg forces have been measured with long force platforms (Komi 1985, Vähäsöyrinki 2008). In skating technique small force plates have been introduced (Komi 1987) and pressure insoles have been used (Stöggl et al. 2010) but a fully functional 3D force measurement system that could be easily changed from one skier to another does not exist at present. The purpose of this study was to design, build and test a light weight mobile force measurement system during skating.